The happening - Shyamalan, M. Night; Wahlberg, Mark, 1971-; Deschanel, Zooey, 1980-; Leguizamo, John.; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
An unstoppable event threatens the world's population by attacking the most basic human instinct of all: survival. Elliot Moore is an ordinary man who is trying to save his family from a terrifying, invisible killer. As Elliot discovers the incredible possibility of what is happening, it becomes very clear that no one is safe.
English track: Dolby digital 5.1.
Spanish and French tracks: Dolby digital surround.
Special features: Deleted scenes with introductions by M. Night Shyamalan; "The hard cut" featurette; "I hear you whispering" featurette; "Visions of The happening: a making-of" featurette; "A day for Night" featurette; "Elements of a scene" featurette; gag reel.
Director of photography, Tak Fujimoto ; editor, Conrad Buff ; music, James Newton Howard.
Mark Wahlberg, Zooey Deschanel, John Leguizamo, Betty Buckley.
MPAA rating: R; for violent and disturbing images.
Keywords: Mass suicide -- Drama; Toxins -- Drama; Families -- Drama; Feature films; Thrillers (Motion pictures); Thrillers (Television programs); Video recordings for the hearing impaired; Mystery films